2021
DOI: 10.3233/ves-201535
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of residual dizziness in patients with benign paroxysmal positional vertigo after successful repositioning: A multi-center prospective cohort study

Abstract: BACKGROUND: While patients with benign paroxysmal positional vertigo (BPPV) commonly develop residual dizziness (RD) after successful repositioning, the factors predictive of RD remain controversial. OBJECTIVE: To identify factors predictive of RD onset in patients with BPPV following successful repositioning. METHODS: This multi-center prospective cohort study enrolled 243 patients with idiopathic BPPV. Vestibular functional and psychological wellbeing assessments administered before repositioning provided th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…RD is considered a complex vestibular disorder and several hypotheses have been proposed to explain its pathophysiology [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Although theoretically valid, none of them has been supported by definitive data, nor do they exclude other causal factors that could play a role in the genesis of RD acting either independently or synergistically.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RD is considered a complex vestibular disorder and several hypotheses have been proposed to explain its pathophysiology [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Although theoretically valid, none of them has been supported by definitive data, nor do they exclude other causal factors that could play a role in the genesis of RD acting either independently or synergistically.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, central adaptation cannot promptly restore the pre-existing condition and produces subtle symptoms consistent with RD. The delayed central adaptation is associated with many factors, such as BPPV duration [ 10 , 11 ], age [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and the subject’s emotional state [ 12 , 13 , 14 ]. Furthermore, it should be considered that aging significantly degrades sensory systems, worsening central processes measuring balance and body perception, therefore predisposing to dizziness and disequilibrium [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that decreased VEMPs response, especially oVEMP abnormality, plays an important role in BPPV occurrence and recurrence. Whereas, only a few studies are focused on VEMP evaluation and RD ( 9 , 11 , 12 , 28 ). The lack of stratified design and limited sample size may explain the inconsistency around whether a decreased or an augmented cVEMP response is truly related to RD as noted in the previous literature.…”
Section: Discussionmentioning
confidence: 99%